Addressing Nanomaterial Immunosafety by Evaluating Innate Immunity across Living Species - Boraschi, Diana; Alijagic, Andi; Auguste, Manon; Barbero, Francesco; Ferrari, Eleonora; Hernadi, Szabolcs; Mayall, Craig; Michelini, Sara; Navarro Pacheco, Natividad I; Prinelli, Alessandra; Swart, Elmer; Swartzwelter, Benjamin J; et al. (Small (Weinheim an der Bergstrasse, Germany), 2020)
The interaction of a living organism with external foreign agents is a central issue for its survival and adaptation to the environment. Nanosafety should be considered within this perspective, and it should be examined that how different organisms interact with engineered nanomaterials (NM) by either mounting a defensive response or by physiologically adapting to them. Herein, the interaction of NM with one of the major biological systems deputed to recognition of and response to foreign challenges, i.e., the immune system, is specifically addressed. The main focus is innate immunity, the only type of immunity in plants, invertebrates, and lower vertebrates, and that coexists with adaptive immunity in higher vertebrates. Because of their presence in the majority of eukaryotic living organisms, innate immune responses can be viewed in a comparative context. In the majority of cases, the interaction of NM with living organisms results in innate immune reactions that eliminate the possible danger with mechanisms that do not lead to damage. While in some cases such interaction may lead to pathological consequences, in some other cases beneficial effects can be identified.
Keywords: hodnocení rizik; nanostruktury; immunosafety; Immunity, Innate; innate immunity; Animals; Adaptive Immunity; Risk Assessment; Nanostructures; evolution; nanomaterials; adaptivní imunita; zvířata; přirozená imunita